(untitled) - Sunoo, Jan Jung-Min (Vietnam, 2007)
The report shows a practical guide for strikes resolves. It is about What are the trends of strikes in Vietnam? Where are strikes occurring and How? Why workers go on strikes? How can employees and employers address the problems of labor relations. What re good practices?
Keywords: Collective labor agreements,Strikes and lockouts,Đình công và phá hoại,Thỏa ước lao động tập thể